Implementasi Model Pembelajaran Kooperatif Team Accelerated Instruction Untuk Meningkatkan Hasil Belajar Akuntansi Pada Kompetensi Dasar Menjelaskan Tahap-Tahap Proses Pencatatan Transaksi Perusahaan Jasa Siswa Kelas X Ak.2 SMK Negeri 1 Dumai Tahun Ajara - Sutihermi Sutihermi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to improve student accounting learning outcomes at SMK Negeri 1 Dumai. This type of research is Classroom Action Research. The subjects in this study were students of class X Accounting. 2 Dumai State Vocational School 1 for the 2021/2022 academic year with a total of 36 students. The tools to be used to collect data are observation sheets and tests. Based on the results of the study, the following data were obtained: 1) The average value of student accounting learning outcomes showed an increase. Before the action as many as 16 people or 44.44% increased in cycle I as many as 24 people or 66.67%. In cycle II there was also an increase of 34 people or 94.44%. 2) Student learning activities are increasing. In the first cycle of the first meeting, the average student activity was only 64.81%. At the second meeting it increased to 77.47%. In cycle II there was another increase, namely to 90.12% with a very good category. So that the average student learning activity becomes 77.47% in the good category. 3) Teacher activity can also improve for the better by applying the Team Accelerated Instruction cooperative learning model. At the first meeting of cycle I, the total score of teacher activity was 37 (67.27%) increasing to 41 (74.54%) at the second meeting. So that the average in cycle I became 70.9%. Then it increased again to 50 (90.9%) in cycle II. The general results of the research show that the implementation of the team accelerated instruction cooperative learning model can improve accounting learning outcomes in basic competencies explaining the stages of the process of recording student service company transactions Class X AK.2 SMK Negeri 1 Dumai Academic Year 2021/2022